Variation of blubber thickness for three marine mammal species in the southern Baltic Sea - Siebert, Ursula; Grilo, Miguel L.; Kesselring, Tina; Lehnert, Kristina; Ronnenberg, Katrin; Pawliczka, Iwona; Galatius, Anders; Kyhn, Line A.; Dähne, Michael; Gilles, Anita (Frontiers in Physiology, 2022)
Evaluating populational trends of health condition has become an important topic for marine mammal populations under the Marine Strategy Framework Directive (MSFD). In the Baltic Sea, under the recommendation of HELCOM, efforts have been undertaken to develop indicator threshold values for blubber thickness (as an indicator of energy reserves) in marine mammals. However, current values lack geographical representation from the entire Baltic Sea area and a large dataset is only available for grey seals (Halichoerus grypus) from Sweden and Finland. However, development of valid thresholds requires knowledge on variation related to geography throughout the investigation area. Blubber thickness evaluation can provide important information about the energy reserves, and hence, food availability in the Baltic Sea. However, methodological standardization to be performed under HELCOM should include relevant datasets with good geographical coverage. In this study, seasonal and temporal trends of blubber thickness were evaluated for three marine mammal species residents in the southern Baltic Sea – harbor seal (Phoca vitulina), grey seal and harbor porpoise (Phocoena phocoena). Additionally, the effects of age, season and sex were analyzed in order to establish? blubber thickness thresholds for individuals displaying good health status. Seasonal variation of blubber thickness was evident for all species, with some species presenting more pronounced effects in specific age categories. Similarly, for harbor seals and porpoises, fluctuations were present over the years included in the analysis. In the seal species, blubber thickness values differed between the sexes. In harbour seals and porpoises blubber thickness values differed between the age classes. Proposed threshold values are presented for the studied species, although a great variability can exist when considering individuals in good health conditions. Furthermore, while an important initial screening tool, blubber thickness assessment cannot be considered a valid methodology for health assessment in marine mammals and should be complemented with data on specific health parameters developed for each species.